2006
DOI: 10.1051/animres:2006023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preconditioning and extrusion of linseed on the ruminal biohydrogenation of fatty acids. 2. In vitro and in situ studies

Abstract: -The extent and/or intermediates of ruminal biohydrogenation (BH) of fatty acids (FA) were investigated in vitro and in situ using a raw, pre-conditioned or extruded blend of linseed and wheat bran (70:30). The duration of in vitro incubations were 2, 4, 8, 16 and 24 h, with 5 replicates. In situ studies used 3 dry ruminally fistulated Holstein cows in a 3 × 3 Latin square design, with 3 weeks adaptation to the linseed form. The diet contained 20% (DM basis) of the linseed based blend. The duration of in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The adequate identification of oleic acid in the batch in vitro incubations under consideration allowed the calculation of the net gain of 18:0 [3] which has been related to the amounts of C 18 PUFA lost. Oleic acid concentrations in 24-h incubations of Akraim et al [2] were not reported and in this case an average BH value of oleic acid (491 g/ kg) has been assumed to calculate the oleic acid remaining after 24 h. The linear relationship revealed that a constant proportion (0.666; Fig. 4) of hydrogenated C18 PUFA was transformed into the saturated end-product, 18:0 ( Fig.…”
Section: In Vitro Simulation Of Production Of Bh Intermediates and Thmentioning
confidence: 98%
See 4 more Smart Citations
“…The adequate identification of oleic acid in the batch in vitro incubations under consideration allowed the calculation of the net gain of 18:0 [3] which has been related to the amounts of C 18 PUFA lost. Oleic acid concentrations in 24-h incubations of Akraim et al [2] were not reported and in this case an average BH value of oleic acid (491 g/ kg) has been assumed to calculate the oleic acid remaining after 24 h. The linear relationship revealed that a constant proportion (0.666; Fig. 4) of hydrogenated C18 PUFA was transformed into the saturated end-product, 18:0 ( Fig.…”
Section: In Vitro Simulation Of Production Of Bh Intermediates and Thmentioning
confidence: 98%
“…This is unlikely as EFA in intact protective structures such as oleosomes probably will be predominant in the lipid residues in the bags, whereas these structures will have been destroyed in the lipids that have left the bags. This could explain both the low BH of PUFA and the low 18:0 proportions in 24-h incubated bags, when compared to in vitro [73] or in vitro and in vivo [2,49] measurements. However, it cannot explain the higher 18:1 trans proportions in the bag residues compared to in vitro or in vivo.…”
Section: In Sacco Techniquementioning
confidence: 99%
See 3 more Smart Citations